Diseño de mobiliario para vivienda unipersonal en Bogotá (2021)
This project focuses on the development of a furniture proposal to boost the habitability of single-person housing in Bogota, with an emphasis on the use of space and the generation of new relationships between the areas that constitute it, as well as alternatives to storage dynamics. and development of domestic activities in a type of housing whose generalization is due to new ways of life that have been adopted by the Millennial generation, which accounts for needs that justify the development of furniture proposals in this direction.